Linking communities to formal health care providers through village health teams in rural Uganda: lessons from linking social capital. Issue 1 (December 2017) - Musinguzi, Laban; Turinawe, Emmanueil; Rwemisisi, Jude; de Vries, Daniel; Mafigiri, David; Muhangi, Denis; de Groot, Marije; Katamba, Achilles; Pool, Robert
Abstract Background Community-based programmes, particularly community health workers (CHWs), have been portrayed as a cost-effective alternative to the shortage of health workers in low-income countries. Usually, literature emphasises how easily CHWs link and connect communities to formal health care services. There is little evidence in Uganda to support or dispute such claims. Drawing from linking social capital framework, this paper examines the claim that village health teams (VHTs), as an example of CHWs, link and connect communities with formal health care services. Methods Data were collected through ethnographic fieldwork undertaken as part of a larger research program in Luwero District, Uganda, between 2012 and 2014. The main methods of data collection were participant observation in events organised by VHTs. In addition, a total of 91 in-depth interviews and 42 focus group discussions (FGD) were conducted with adult community members as part of the larger project. After preliminary analysis of the data, we conducted an additional six in-depth interviews and three FGD with VHTs and four FGD with community members on the role of VHTs. Key informant interviews were conducted with local government staff, health workers, local leaders, and NGO staff with health programs in Luwero. Thematic analysis was used during data analysis. Results The ability of VHTs to link communities with formal health care was affected by the stakeholders' perception of their roles. Community members perceive VHTs as working for and under instructions of "others", which makes them powerless in the formal health care system. One of the challenges associated with VHTs' linking roles is support from the government and formal health care providers. Formal health care providers perceived VHTs as interested in special recognition for their services yet they are not "experts". For some health workers, the introduction of VHTs is seen as a ploy by the government to control people and hide its inability to provide health services. Having received training and initial support from an NGO, VHTs suffered transition failure from NGO to the formal public health care structure. As a result, VHTs are entangled in power relations that affect their role of linking community members with formal health care services. We also found that factors such as lack of money for treatment, poor transport networks, the attitudes of health workers and the existence of multiple health care systems, all factors that hinder access to formal health care, cannot be addressed by the VHTs. Conclusions As linking social capital framework shows, for VHTs to effectively act as links between the community and formal health care and harness the resources that exist in institutions beyond the community, it is important to take into account the power relationships embedded in vertical relationships and forge a partnership between public health providers and the communities they serve. This will ensure strengthened partnerships and the improved capacity of local people to leverage resources embedded in vertical power networks.